MODERN STRATEGIES FOR THE TREATMENT OF SECRETORY OTITIS MEDIA IN PATIENTS WITH POST-COVID SYNDROME - Bezeha, M.I. (World of Medicine and Biology, 2025)
The purpose of the study was to evaluate the use of topical corticosteroid therapy as a promising method of treating patients with post-COVID secretory otitis media. A prospective, open-label study was conducted in 28 patients (mean age 36.4±8.7 years) with secretory otitis media lasting more than three weeks. Clinical outcomes were assessed using otoscopy, tympanometry, audiometry and symptom scales at baseline, 1 week, 4 weeks, 12 weeks and 6 months. During the observation period, it was proved that local administration of betamethasone dipropionate in the area of the tuberous roller is a promising additional treatment for secretory otitis media in patients with COVID-19 and demonstrates better clinical outcomes compared to standard therapy.